The Influence of CSR, Board Gender Diversity, and Cash Holding towards Company Value: Case Study of the Company Listed on the SRI-KEHATI Index on the Indonesia Stock Exchange 2018-2023 - Ester Tri Utami; Irma Paramita Sofia (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
In the rise of sustainable and responsible investment, this study aims to analyze and provide empirical evidence about the importance of firm’s CSR activities, board gender diversity, and cash holding in shaping the firms’ value. Those variables aligned with the firm’s performance of social and environmental, corporate governance, and financial aspect, thus suitable to be further analyzed with the study object. This research uses objects of firms listed in SRI-KEHATI Index listed on Indonesia Stock Exchange during 2018 – 2022. Purposive method is used to select the sample, then the secondary data is collected from Indonesia Stock Exchange and companies’ website before analyzed quantitatively by using E-views. This research shows evidence that CSR, board gender diversity, and cash holding have significant effect on firm value simultaneously. However, partial testing shows that only the board gender diversity is significantly affected firm value while CSR and cash holding are not. Besides contributing to the literature, this result shows the necessity of firm to perform the best managerial decision in social and environmental, corporate governance, and financial policy as whole. Especially, the diversity of board which plays an important role in governing the firms. This implication also applies to the regulator and investor, in which every stakeholder can encourage awareness of those aspects to maximize the value of sustainable investment.